STRATEGI SALURAN DISTRIBUSI DAN PROMOSI DALAM MENDUKUNG PERTUMBUHAN EKONOMI KREATIF DI KABUPATEN BENGKALIS - Tri Handayani, Tri Handayani; Supriati; Pretti Ristra (ABEC Indonesia, 2023)
This research aims to find out how consumers perceive the distribution channel and promotion that have been carried out by creative economy entrepreneurs in Bengkalis Regency, then explain how to improve distribution channel and promotion strategies in supporting creative economic growth in Bengkalis Regency. This research is descriptive by distributing questionnaires to 100 respondents. Then the analysis is carried out using frequency distribution tables and calculating the average value (mean) to calculate the frequency of data from each category to find out the categories of respondents' responses to each of these variables and indicators. The results of the study show that creative economy entrepreneur have implemented local distribution channel and promotion strategies that are local (regional) scale, so that creative economic products are still enjoyed by local consumers. Strategy improvement that can be done is to improve distribution channel strategies on a national and international scale by increasing government regulations, creating distribution access by the government, creating creative space, and business assistance through sustainable mentoring.